Is Homo Economicus Dead and Should We Mourn His Death? How ESG is Changing the Way of Thinking about Human in Economics and Economy - Nowak , Karolina (Sensus Historiae, 2024)
The popularization of the idea of sustainable development has led to the introduction of new regulations by the European Union in the form of the Corporate Sustainable Reporting Directive (CSRD), based on ESG (Environmental, Social and Corporate Governance), which create a different framework for the functioning of business entities. The aim of the article is to indicate to what extent the concept of homo economicus is still a sufficient mental construct for formulating a response to the challenges (especially climate) of the modern world, as well as whether it still allows to give meaning to all activities undertaken in the economic sphere. A cultural perspective has been used by the author